The text of the Old Testament an introduction to the Biblica Hebraica - Wurthwein, Ernst, 1909-; Rhodes, Errol F. (Grand Rapids, MI Eerdmans, 1988)
Includes bibliographical references and index.
First published as Der Text des Alten Testaments
Keywords: Bible. O.T. -- criticism, textual; Bible. O.T. -- manuscripts